Successful management of generalized pustular psoriasis with cyclosporine in HIV-infected patient - Deltania, Rasinta Ayudya; Yuniaswan, Anggun Putri (Journal of General - Procedural Dermatology and Venereology Indonesia, 2025)
Background: Generalized pustular psoriasis (GPP) can be associated with human immunodeficiency virus (HIV) infection, making its management more challenging and complex. This case report aims to evaluate the effectiveness and safety of cyclosporine in HIV-associated GPP. Case illustration: A 31-year-old male with a six-year history of HIV on antiretroviral therapy presented with rapidly spreading erythematous plaques with scaling and patches, along with “lakes of pus”, involving 50% of the body surface area (BSA). He reported oral burning, dysgeusia, and odynophagia; tongue Gram stain showed budding yeast and pseudohyphae. The patient was diagnosed with GPP and oral candidiasis in the setting of HIV. Cyclosporine was started at 2.5 mg/kg/day and escalated to 5 mg/kg/day; supportive care included nystatin 4x400,000 IU (swish-and-retain), paracetamol 3x500 mg, 0.9% NaCl wet compresses to pustular areas, emollients for xerosis, and intravenous 0.9% NaCl for hydration. By day 9, BSA improved from 50% to 12% with no severe adverse effects, only fatigue and loss of appetite. Discussion: GPP, a rare severe psoriasis variant, may be exacerbated in HIV patients due to immune dysregulation and CD4+ T-cell decline. In this case, cyclosporine treatment and supportive care improved symptoms without severe adverse effects. Cyclosporine appeared effective with minimal infection risk compared to methotrexate. This case highlights the importance of tailored, cautious immune suppression to manage GPP in HIV and balancing efficacy with infection risk. Conclusion: Cyclosporine may be an effective option for managing GPP in HIV-infected patients with CD4+ decline when used cautiously with close monitoring for opportunistic infections.